Sistem Kewarisan Adat Suku Alas Perspektif Hukum Islam: (Studi Kasus di Kabupaten Aceh Tenggara) - Malik, Imam; Abdullah; Annisa, Priti; Yanti, Izqi (Yayasan Madinah Al-Aziziyah, 2022)
The customary law of the Alas tribe in Southeast Aceh stipulates that male heirs hold exclusive rights to inheritance, as they are considered responsible for their extended families, while women are viewed merely as complements and excluded from inheritance. This practice contradicts the provisions of Islamic law outlined in the Qur'an. This study aims to explore the inheritance practices within the Alas community and analyze them from the perspective of Islamic law. This field research employs a descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the Alas community continues to adhere to the tradition in which women do not receive inheritance. This practice is justified by mutual consent reached through deliberations among the heirs. Although the tradition is preserved, it conflicts with Islamic law, which mandates a fair distribution of inheritance between men and women.